Approximation Property of the Stationary Stokes Equations with the Periodic Boundary Condition - Soon-Mo Jung; Jaiok Roh (Journal of Function Spaces)
In this paper, we will consider the stationary Stokes equations with the periodic boundary condition and we will study approximation property of the solutions by using the properties of the Fourier series. Finally, we will discuss that our estimation for approximate solutions is optimal.